A Modification of the Wu and Hoak Method for the Determination of Platelet Aggregates and Platelet Adhesion - Bowry, Sudhir K; Prentice, Colin R M; Courtney, J M (Thrombosis and Haemostasis, 1985)
The Wu and Hoak method for determining circulating platelet aggregates has poor reproducibility; problems have been reported with the composition of the buffer systems, haemolysis, the effects of blood collection technique and a divergence of the platelet aggregate ratio in blood for healthy donors from the theoretical value of 1. Our investigations suggest that the original technique is highly operator-dependent, especially the collection of blood and the method of counting platelets after centrifugation. We describe an improved modification of the Wu and Hoak technique; a new buffer system has been developed and the proportion of blood in the buffered EDTA and buffered EDTA- formalin solutions has been altered to obtain platelet rich plasma. The platelet aggregate ratio (PAR) by this modified method for healthy donors in two different studies was 0.97 ± 0.02 and 0.98 ± 0.01 respectively. Finally, the principle of Wu and Hoak was used to measure accurately platelet adhesion, without the role of platelet-platelet interactions (aggregation). Platelet adhesion and aggregation were then used to evaluate the thrombogenicity of various artificial surfaces, including silicone rubber and polytetra- fluoroethylene (PTFE) vascular grafts.
Keywords: Platelet aggregation; Adhesion; Artificial surfaces